2020
DOI: 10.1186/s12885-020-07195-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in stage at diagnosis and preoperative radiotherapy in patients with rectal cancer

Abstract: Background: Few studies have examined gender differences in the clinical management of rectal cancer. We examine differences in stage at diagnosis and preoperative radiotherapy in rectal cancer patients. Methods: A prospective cohort study was conducted in 22 hospitals in Spain including 770 patients undergoing surgery for rectal cancer. Study outcomes were disseminated disease at diagnosis and receiving preoperative radiotherapy. Age, comorbidity, referral from a screening program, diagnostic delay, distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…If these gender differences are not clinically justifiable, their elimination might enhance survival. 45 8 Further investigation of sex hormones and their association with the efficacy of cancer immunotherapy should be the focus of larger clinical trials to evaluate these parameters as possible prognostic markers. 46 8 Subgroup analyses are important and should be conducted to provide evidence of sex-linked pharmacogenomic markers that should be further studied in larger cohorts of patients.…”
Section: Resultsmentioning
confidence: 99%
“…If these gender differences are not clinically justifiable, their elimination might enhance survival. 45 8 Further investigation of sex hormones and their association with the efficacy of cancer immunotherapy should be the focus of larger clinical trials to evaluate these parameters as possible prognostic markers. 46 8 Subgroup analyses are important and should be conducted to provide evidence of sex-linked pharmacogenomic markers that should be further studied in larger cohorts of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors are contributing to the observed differences of the advanced stage of bladder cancer between sexes; Firstly, it has been reported that most women with visible haematuria which is the common sign for urinary bladder cancer delay in seeking medical care for diagnosis, possibly due to confusion with menses [ 23 , 57 , 69 ]. Secondly, the thinner bladder wall in females and hormonal differences have been contributing to the variation in grades of urinary bladder cancer between sexes as discussed elsewhere [ 31 , 36 , 38 , 53 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to sex differences in the psychological and physical effects of the disease [ 62 ], and differences in treatment strategies for various reasons like gender bias (where no apparent medical reason justifies why female patients are not offered the same treatment as males [ 63 ]). For example, a recent study showed that female rectal cancer survivors were less likely to receive preoperative radiotherapy than male survivors of the same age, level of comorbidity, and tumor depth [ 64 ]. Furthermore, female survivors have been associated with greater cancer-related distress [ 65 ].…”
Section: Discussionmentioning
confidence: 99%